Comparative analysis of components of university adjustment of medical students studying on different financial basis - Yu. N. Timofeeva (Вестник университета)
The purpose of the study is to conduct empirical and statistical evaluation, as well as subsequent comparative analysis of the expression of university adaptation components (social, didactic, and professional) in 1st year medical students studying on different financial basis (commercial, budgetary, and target contract). The scientific novelty of the study lies in the research of medical students’ adaptation processes in the context of their financial basis of education. The online testing method with the subsequent statistical analysis of the obtained data has been applied. To identify the level of expression of the university adaptation components, the method “Students’ adaptation to university” by M.S. Yurkina was used as a diagnostic tool. According to the obtained data, there are statistically significant differences in the levels of expression of the university adaptation components in 1st year medical students studying on a different financial basis. The least psychologically stable from the point of view of social infusion into the university environment are the students studying under the target contract. Didactic and professional adaptation components in higher education are least expressed in students studying on a commercial basis. The data obtained as a result of the study can be used in university educational activity to improve freshmen’s adaptation processes management considering the financial basis of their education, which will optimize the issue of preserving the contingent of students.